Effectiveness of Telecare in Reducing Stress Patients with Chronic Diseases - Imas Yoyoh; Abdul Syafei; Apriani; Dedi Pahrul (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Chronic diseases such as diabetes mellitus, hypertension, and heart failure require long-term management that often leads to psychological stress in patients. In Bogor City, limited access to face-to-face healthcare services and the burden of routine medical visits may further increase stress levels. Telecare, a remote healthcare model based on communication technology, offers a potential solution to enhance continuous psychosocial support and health monitoring. This study aimed to analyze the effectiveness of telecare in reducing stress levels among patients with chronic diseases in Bogor City. A quasi-experimental design with a pretest-posttest control group approach was employed. A total of 60 patients were selected using purposive sampling, consisting of 30 respondents in the intervention group (receiving telecare for 8 weeks) and 30 in the control group (receiving standard care). Stress levels were measured using the Perceived Stress Scale (PSS-10). Data were analyzed using paired t-tests and independent t-tests with a significance level of 0.05. The results showed a significant reduction in stress scores in the intervention group (24.6 ± 4.2 to 16.8 ± 3.9; p<0.001), while the control group showed no significant change (p=0.087). Telecare was effective in reducing stress levels and can be implemented in primary healthcare settings to improve patients’ psychological well-being.